18th AIAA Computational Fluid Dynamics Conference 2007
DOI: 10.2514/6.2007-4464
|View full text |Cite
|
Sign up to set email alerts
|

On Obtaining High-Order Finite-Volume Solutions to the Euler Equations on Unstructured Meshes

Abstract: High-order finite volume schemes for unstructured meshes first appeared in the literature at least as early as Barth and Frederickson's 1990 paper. 1 However, the approach has not gained a wide following, perhaps because of the difficulties in achieving a genuinely high-order accurate solution, especially when dealing with curved boundaries. In this paper, we document in detail our approach to constructing a high-order solver. In addition to reconstruction, we discuss flux integration and curved boundary treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 18 publications
(22 reference statements)
0
44
0
Order By: Relevance
“…However, by using these techniques it is no easy to find convergence orders higher than two. The k-exact reconstruction [18,163,164] is based on the computation of a polynomial expansion inside each cells that preserves the mean of the variable in that cell. This polynomial expansion reconstructs exactly polynomials up to order k. The coefficients defining this polynomial are chosen by minimization, in the Least-Squares sense, of the difference between the averages of the reconstructing polynomial and the actual averages.…”
Section: The Fv-mls Methodsmentioning
confidence: 99%
“…However, by using these techniques it is no easy to find convergence orders higher than two. The k-exact reconstruction [18,163,164] is based on the computation of a polynomial expansion inside each cells that preserves the mean of the variable in that cell. This polynomial expansion reconstructs exactly polynomials up to order k. The coefficients defining this polynomial are chosen by minimization, in the Least-Squares sense, of the difference between the averages of the reconstructing polynomial and the actual averages.…”
Section: The Fv-mls Methodsmentioning
confidence: 99%
“…This reconstruction can be found in some mean-conservation restrictions used in other cell averaged finite volume method schemes, see [31,32] for instance. In our case, the mean-conservation correction appears a posteriori in the reconstruction contrary to the k-exact method for example, in which a priori mean-conservation restriction is imposed.…”
Section: Time-dependent Term Treatmentmentioning
confidence: 97%
“…While ''everyone knows" that curved boundaries must be used to obtain genuinely high-order solutions, there is essentially no discussion in the literature on what level of accuracy is required, or how to get it. We have shown [37,33,35] that the common knowledge is correct: the order of accuracy of the boundary shape must equal the order of accuracy of the solver. In addition, we have shown that Gauss point locations along the boundary must be spaced by arc length rather than being projections of Gauss points from a polygonal boundary representation onto the curved boundary [35].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown [37,33,35] that the common knowledge is correct: the order of accuracy of the boundary shape must equal the order of accuracy of the solver. In addition, we have shown that Gauss point locations along the boundary must be spaced by arc length rather than being projections of Gauss points from a polygonal boundary representation onto the curved boundary [35]. Finally, treatment of shocks and other solution discontinuities requires particular attention for high-order schemes, both to eliminate overshoots at discontinuities and to avoid ruining accuracy in smooth regions of the flow while retaining good convergence properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation